Soil pollution : from monitoring to remediation - Duarte, Armando C.; Cachada, Anabela; Rocha-Santos, Teresa (Academic Press, an imprint of Elsevier, 2018)
This book provides comprehensive information on soil pollution, including causes, distribution, transport, the transformation and fate of pollutants in soil, and metabolite accumulation. It covers organic, inorganic and nanoparticle pollutants and methodologies for their monitoring, and features a critical discussion on ecotoxicological and human effects of soil pollution, and strategies for soil protection and remediation.